SO2 EMISSION MEASUREMENT BY DOAS (DIFFERENTIAL OPTICAL ABSORPTION SPECTROSCOPY) AND COSPEC (CORRELATION SPECTROSCOPY) AT MERAPI VOLCANO (INDONESIA) - Hanik Humaida (Indonesian Journal of Chemistry, 2008)
The SO2 is one of the volcanic gases that can use as indicator of volcano activity. Commonly, SO2 emission is measured by COSPEC (Correlation Spectroscopy). This equipment has several disadvantages; such as heavy, big in size, difficulty in finding spare part, and expensive. DOAS (Differential Optical Absorption Spectroscopy) is a new method for SO2 emission measurement that has advantages compares to the COSPEC. Recently, this method has been developed. The SO2 gas emission measurement of Gunung Merapi by DOAS has been carried out at Kaliadem, and also by COSPEC method as comparation. The differences of the measurement result of both methods are not significant. However, the differences of minimum and maximum result of DOAS method are smaller than that of the COSPEC. It has range between 51 ton/day and 87 ton/day for DOAS and 87 ton/day and 201 ton/day for COSPEC. The measurement of SO2 gas emission evaluated with the seismicity data especially the rockfall showed the presence of the positive correlation. It may cause the gas pressure in the subsurface influencing instability of 2006 eruption lava.